The influence of personality trait dimensions on individual knowledge sharing behaviour - Maliheh Lotfi, 1986- author; Syaharizatul Noorizwan Muktar; Fakulti Pengurusan (2014)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2014